Managed retreats by whom and how? Identifying and delineating governance modalities - Hanna C; White I; Glavovic BC (Elsevier B.V, 2021)
Managed retreat has become a compelling policy imperative as climate change exacerbates socio-natural hazard risks and imminent harm looms for exposed communities. Retreats may be initiated over different times and scales using various instruments by actors, from the state to the private sector and civil society. However, in the absence of a coherent strategic vision, guiding frameworks, and capacity to manage retreats, at-risk communities, their elected representatives, policy makers, and planners are compelled to embark on retreat governance experiments. Consequently, retreat is perceived as a ‘high regrets’ policy imperative with potentially adverse impacts for community wellbeing, as well as political and professional risks. To help translate managed retreat rhetoric into reality, this paper presents a governance framework that acknowledges the multiplicity of ‘managed retreats.’ Using examples from Aotearoa-New Zealand, we identify and delineate retreat modalities and clarify terminology, converging our framework with the international mobility literature to harness the valuable lessons from decades of human mobility practice.
Keywords: Managed retreat; Strategic planning; Governance; Resilience; Climate change; Risk reduction; Adaptation; Relocation